Risk Factors of Stunted Children Aged 0-23 Months at Jatibaru Public Health Center Bima, West Nusa Tenggara: A Case Control Study - Atmalia, Khafifah Puja; Balfas, Rania Reiza Faris; Aryana, Nurfathonah; Wulandari Hidaya; Putri, Nina Dwi (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Nutritional status in children under-five profoundly affects linear growth, cognitive development, and long-term disease. Stunting, defined as a child being too short for their age, results from prolonged malnutrition, particularly in the first 1000 days. In West Nusa Tenggara (NTB), stunting prevalence is the fourth highest at 32.7%, with 31.2% affected in Bima. This study aims to compare previous exposure between stunted children and non - stunted children in primary health care settings in Bima. Methods: A case-control study was conducted involving children aged 0–23 months who accessed integrated health services, bring a Maternal and Child Health Book (MCH), and had recorded health data at the Jatibaru Primary Health Center. Children with congenital anomalies were excluded. Maternal and child-related risk factors were assessed through anthropometric measurements (WHO standards) and structured interviews with validated questionnaire. Bivariate analysis (Chi-square, p < 0.25) was followed by multivariate logistic regression (p < 0.05). Result: A total of 124 participants were included (62 cases, 62 controls). Multivariate analysis revealed that maternal factors significantly associated with stunted growth in children were poor nutritional status (AOR 7.519, p = 0.000) and low nutrition knowledge (AOR 6.930, p = 0.000). Among child-related factors, stunted children were significantly associated with low birth weight (AOR 17.013, p = 0.000) and inadequate breastfeeding (AOR 7.434, p = 0.006). Conclusion: The mother’s nutritional status and children’s birth weight are the main risk factors of stunted children. Targeted interventions addressing maternal education and perinatal care are recommended to reduce stunting prevalence.